2022
DOI: 10.1093/geroni/igac015
|View full text |Cite
|
Sign up to set email alerts
|

Using a Nature-Based Virtual Reality Environment for Improving Mood States and Cognitive Engagement in Older Adults: A Mixed-Method Feasibility Study

Abstract: Background and Objectives Exposure to nature and nature-based imagery has been shown to improve mood states and stave off cognitive decline in older adults. Even “micro-doses” of natural scenery can provide beneficial effects in situations where more extensive interactions with nature are not feasible. In the current study we evaluated the use of virtual reality (VR) for delivering interactive nature-based content with the goal of prompting active engagement and improving mood states in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 69 publications
3
32
1
1
Order By: Relevance
“…Specifically, the applied intervention significantly reduced the symptoms of depression by 46%, 21%, and 24% for stroke, cardiac, and pulmonary patients, respectively, suggesting that the intervention could be effective in patients with different medical conditions (Rutkowski et al 2021 ; Jóźwik et al 2021 ; Szczepańska-Gieracha et al 2021b ; Kiper et al 2022 ). Other studies using VR greenery have shown similar effectiveness (Boffi et al 2022 ): Chan et al ( 2021 ) showed that a short walk in a virtual forest improved the emotional state of the elderly; a recent mixed-method feasibility study demonstrated the usefulness of different nature-based VR environments in mood improvement (Kalantari et al 2022 ); and the use of the VR garden idea had positive effects on affect, well-being and stress in the face of isolation related to the COVID-19 pandemic (Malighetti et al 2022 ; Meyer et al 2022 ; Pallavicini et al 2022 ). Nevertheless, the main difference between the above research and this study was the additional implementation of psychotherapeutic elements in our intervention.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, the applied intervention significantly reduced the symptoms of depression by 46%, 21%, and 24% for stroke, cardiac, and pulmonary patients, respectively, suggesting that the intervention could be effective in patients with different medical conditions (Rutkowski et al 2021 ; Jóźwik et al 2021 ; Szczepańska-Gieracha et al 2021b ; Kiper et al 2022 ). Other studies using VR greenery have shown similar effectiveness (Boffi et al 2022 ): Chan et al ( 2021 ) showed that a short walk in a virtual forest improved the emotional state of the elderly; a recent mixed-method feasibility study demonstrated the usefulness of different nature-based VR environments in mood improvement (Kalantari et al 2022 ); and the use of the VR garden idea had positive effects on affect, well-being and stress in the face of isolation related to the COVID-19 pandemic (Malighetti et al 2022 ; Meyer et al 2022 ; Pallavicini et al 2022 ). Nevertheless, the main difference between the above research and this study was the additional implementation of psychotherapeutic elements in our intervention.…”
Section: Discussionmentioning
confidence: 88%
“…For example, recent work has investigated a range of topics in relation to the built environment, including the importance of biophilic workspaces (Dravigne et al, 2008; Dreyer et al, 2018), features of mental and behavioral health facilities (Shepley et al, 2022), and the relationship between green spaces and crime (Bogar & Beyer, 2015; Sadatsafavi et al, 2022; Shepley et al, 2019). When examining digital spheres, those that have been assessed most often in terms of VR technologies include people’s experiences within digital worlds (e.g., Kalantari et al, 2022) and the evaluation of alternative physical design decisions (e.g., Dunston et al, 2011). However, the intermingling of virtual and physical environments noted above also necessitates research into the behavioral implications of our hybrid worlds.…”
Section: Behavioral and Design Implications Of The Physical–virtual C...mentioning
confidence: 99%
“…Few studies have focused on social or enjoyment applications, involved randomized trials, included long-term follow-up, and there has been limited attention to usability issues (e.g., Dermody et al, 2020; Lee et al, 2019). In this regard, our group (Kalantari et al, 2022) recently completed a pilot feasibility trial to evaluate the use of VR for delivering interactive nature-based content with the goal of prompting active engagement and improving mood among aging adults with and without impairments. Overall, the findings indicated significant improvements in mood after exposure to the VR and in attitudes toward the technology.…”
Section: Artificial Intelligence and Aging Adultsmentioning
confidence: 99%